Description of Dermatitis Complaints in Fisherman in Oesapa Village Kupang City - Djula, Fitri E.; Berek, Noorce Ch.; Dodo, Dominirsep O. (Timorese Journal of Public Health, 2024)
Fishermen are people who carry out fishing activities on the surface of sea water, brackish water and fresh water, fishermen who catch fish are very likely to experience accidents due to work and occupational diseases. Skin diseases that occur in fishermen due to the concentration of sea water which can affect the skin. Seawater has irritating properties that can cause chronic dermatitis. Prevention that can be done to reduce the occurrence of skin diseases is by using PPE at work and improving personal hygiene before and after work. The aim of this study was to determine the factors of using PPE and personal hygiene with complaints of dermatitis in fishermen at RT 031 Oesapa Village, Kupang City. This type of research is descriptive research. The sampling technique used a total sampling technique totaling 35 fishermen who were in RT 031 Oesapa Village, Kupang City. The results of the study found that good personal hygiene factors were 11 (31.4%) and bad personal hygiene were 24 (68.6%), bad personal hygiene had complaints of dermatitis by 17 people (48.6) and no complaints as many as 7 people (20%), while fishermen with good personal hygiene had complaints of dermatitis as many as 9 people (25.7%), 25 (71.4%) bad use of PPE and 10 (28.6%) good , clinical symptoms had no complaints as many as 9 people (25.7%) and those who had complaints were as many as 26 people (74.3%). Fishermen need to complete the use of PPE and maintain personal hygiene before and after doing work so they can avoid occupational diseases and can do work efficiently.